Poa bashkirica (Poaceae): a new grass species from the southern Ural Mountains, Russia - Olonova, Marina V. (Phytotaxa, 2025)
Pоа bashkirica, a new species from Bashkiria, South Ural (Russia) is described and illustrated. Morphologically, it is similar to P. korshinskyi, P. transbaicalica and P. argunensis but differs from the first two species with lemmas, pubescent between veins, and from P. argunensis with the distribution. From all mentioned species it differs by culms purple at the base.